Implementasi Kombinasi Enkripsi Base64 Dengan Hashing Sha-1 Dan Md5 Pada Aplikasi Perpustakaan Universitas Muhammadiyah Bengkulu - Andilala, Andilala; Hidayah, Agung Kharisma; Mahfuzy, AR. Walad; Oki, M. (Jurnal Teknologi Sistem Informasi dan Sistem Komputer TGD, 2023)
One of the aspects of information security that can be done for a system is by adding security to a system, if using Base64 with static Sha-1 and Md5 hashing there is little possibility of data theft by hackers because they have been given layered security, to apply base64 with hashing-1, a cryptographic science mechanism is needed in it. Lately, many universities in the library unit section have placed web-based applications on the internet as a medium for displaying information systems that are very cheap, many activities can be carried out by users on these presentation media, such as accepting registration for new library members, ordering books, presentation of scientific journals, presentation of student final assignments (thesis, theses and dissertations) and others. Data security that still uses the usual method often causes several problems, such as being exposed to attacks and break-ins by hackers which can result in leaks and loss of existing data. This problem arises because there is no security system for library applications, the purpose of this research is to implement security for the library system by implementing a combination of Base64 encryption with sha-1 and MD5 hashing so that important data contained in the library unit is safe from leaks. After implementing the collaborative use of Base64 with sha-1 and MD5 hashing, the results of hacking a simple Python script to test a brute force attack for testing password storage security using a combination of Base64 encryption and SHA-1 and MD5 hashing on library applications with after results testing a brute force attack on the Visual Studio Code (VSC) application, the results obtained are "Passwords do not match", this result indicates that the collaboration of several algorithms was successful.